BIOLOGICAL REMEDIATION OF CYANIDE: A REVIEW - Karamba Kabiru Ibrahim; Mohd Arif Syed; Mohd Yunus Shukor; Siti Aqlima Ahmad (SEAMEO BIOTROP, 2015)
Cyanide and its complexes are produced worldwide as industrial waste or effluents. Biodegradation is considered the most economical and effective method for removing cyanide from the environment. Numerous studies have identified various microorganisms capable of degrading cyanide under natural conditions. Hydrolytic, oxidative, reductive, and substitutive/transfer reactions are among the most common pathways utilized by microorganisms during cyanide degradation. Biodegradation may occur under aerobic or anaerobic conditions, depending on environmental factors. The use of immobilized microorganisms or purified enzymes has also been shown to increase degradation efficiency. Several microbial species, including Klebsiella oxytoca, Corynebacterium nitrophilum, Brevibacterium nitrophilum, Bacillus spp., Pseudomonas spp., Rhodococcus spp., and strain UKMP-5M, have been reported to be highly effective in cyanide biodegradation.